MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN 1-10 MELALUI LILIN ANGKA BAGI TUNAGRAHITA RINGAN - Raudah - (Jurnal Penelitian Pendidikan Khusus, 2012)
The research was motivated by the problems faced by children who have difficulty Tunagrahita Lightweight familiar symbol numbers 1 to 10. To overcome this problem, the researcher helped the media wax figures. This type of research is that the researchers use Single Subject Research (SSR) is a study done under different conditions using AB design. Type the target size is the frequency of their behavior by counting the number of correct answers by using the analysis of visual data analysis graph that consists of the analysis of the condition and between conditions. The results of this study states increased ability to recognize the symbol numbers 1 to 10. In the Baseline condition of the child's ability to read as much as 3 numbers, indicate the appropriate commands and write down as much as 2 number 3 number. And the literacy intervention conditions increased to 10 numbers, showed the ability to increase to 10, and writing skills increased to 10 numbers. As well as on the analysis of the condition and between conditions found that the estimated trend direction, trend stability, trace data and the increased level changes positively and overlape data on the analysis of the smaller inter-condition, it is proved that the Media Can Improve Ability Wax Figures Coat Know Numbers 1 Up to 10 Tunagrahita Light for Children.